Designing a Conceptual Digital Twin Architecture for High-Temperature Heat Upgrade Systems - Alexandru Matei; Alex Butean; Constantin-Bala Zamfirescu; José Daniel Marcos (Applied Sciences)
Industrial processes often rely on high-temperature heat, traditionally generated through the combustion of fossil fuels. However, a significant shift towards renewable and sustainable heat sources is underway, supported by environmental policies and actions such as the European Green Deal. These renewable energy systems are complex and characterized by a high degree of interdependencies between various parameters. Optimizing and orchestrating these processes for efficient heat delivery requires careful consideration of factors such as temperature levels, flow rates, and energy demands. Traditional methods often struggle to handle the complexity of these systems, hindering efforts to maximize efficiency and minimize energy waste. This paper addresses these challenges by proposing a modular digital twin framework tailored for high-temperature heat upgrade systems. By integrating with the physical heat upgrade system, the digital twin can create a dynamic and continuously updated representation of its behavior, while also providing additional advantages such as improved process simulation, predictive capabilities, enhanced design, and system integration. Using the SUSHEAT project as a case study, this work advances digital twin methodologies by introducing an architecture applicable in the early product lifecycle phases, addressing a gap in current research.